Market liquidity : Theory, evidence, and policy - Foucault, Thierry; Pagano, MarcoRoell, Ailsa (New York : Oxford University Press, 2023)
The way in which securities are traded is very different from the idealized picture of a frictionless and self-equilibrating market offered by the typical finance textbook. Market Liquidity offers a more accurate and authoritative take on liquidity and price discovery. The authors start from the assumption that not everyone is present at all times simultaneously on the market, and that even the limited number of participants who are have quite diverse information about the security's fundamentals. As a result, the order flow is a complex mix of information and noise, and a consensus price only emerges gradually over time as the trading process evolves and the participants interpret the actions of other traders. Thus a security's actual transaction price may deviate from its fundamental ...
Keywords: Business Economics and Finance; Risk Management